Speech act and experiential analysis of Bali netizen reactions to the pandemic regulation posts - Putu Nur Ayomi; Komang Dian Puspita Candra; I Komang Sulatra (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
Social media has enabled individuals to publicly express their feelings, opinions, or sentiments about specific issues, including government policies. The accumulation of similar views from social media users can represent how the public perceives certain matters. The research was done by analysing netizen comments on posts regarding the pandemic regulation in Bali from August to November 2021 in a popular Instagram local news account Infodenpasar. The research employs the theory of speech act to describe the illocutionary force of netizen utterances to express particular sentiments and the systemic functional theory about experiential metafunction to explore the construal of participants and actions in the discourse. The finding shows that the most dominant speech act is conflictive, which expresses disbelief, complaint, and skepticism. In addition, the events in the clauses are constructed with various processes and participant types, especially relational process